EFEKTIVITAS DAYA HAMBAT BAKTERI EKSTRAK BAWANG DAYAK TERSTANDARISASI FLAVONOID TERHADAP Enterococcus Faecalis (In vitro) - Ferdio Armanda; Muhammad Yanuar Ichrom Nahzi; Lia Yulia Budiarti (Dentino : Jurnal Kedokteran Gigi, 2017)
Background: Enterococcus faecalis is a bacterium which most often found on the wall of the root canal after the root canal treatment. It can be eliminated by NaOCl solution with high concentrations of 5,25%, this can cause toxic effects of the network around it. Dayak onion (Eleutherine palmifolia (L) Merr ) has antibacterial substances resulting active compound content one of it is flavonoid. Purpose: This study aims to determine the differences antibacterial activity of Dayak onion bulb which contains flavonoid compound on the growth of Enterococcus faecalis. Method: This experimental research using post test only with group design with 6 treatments groups, namely Dayak onion bulb extract 20 mg/ml, 40 mg/ml, 60 mg/ml and 80 mg/ml with 5,25% NaOCl as positive control and ethanol 96%as negative control. Result: The results of calculation inhibitory zone obtained the most effective concentration is 80 mg/ml of 21,314 mm,which is the category of high inhibitory zone, but no bacterial growth higher than the NaOCl 5,25% with a mean inhibition zone is 24,416 mm. The analysis data using shpiro-wilk to test a normality test and homogeneity test using levene’s test data showed normal and homogeneous (p<0,05). The analysis data is using one way Anova test that show there is significant differences p=0,000 (p<0,05), then further post hoc LSD test showed significant differences between concentrations of extract of Dayak onion bulb, NaOCl 5,25% and ethanol 96% p=0,000 (p<0,05). Conclusion: there are differences in the antibacterial activity of dayak onion bulb which contains flavonoid compounds on the growth of enterococcus faecalis and inhibitory zone obtained the most effective concentration is 80 mg/ml of 21,314 mm, but no bacterial growth higher than the NaOCl 5,25% with a mean inhibition zone is 24,416 mm.